2018
DOI: 10.3389/fnins.2018.00341
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Promotes Nerve Regeneration via Activation of p300 Acetyltransferase-Mediated VEGF Signaling in a Rat Model of Sciatic Nerve Crush Injury

Abstract: Peripheral nerve injuries are generally associated with incomplete restoration of motor function. The slow rate of nerve regeneration after injury may account for this. Although many benefits of resveratrol have been shown in the nervous system, it is not clear whether resveratrol could promote fast nerve regeneration and motor repair after peripheral nerve injury. This study showed that the motor deficits caused by sciatic nerve crush injury were alleviated by daily systematic resveratrol treatment within 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 75 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…Although SIRT1 is essential for coronavirus replication and survival [113], RSV instead inhibits coronavirus replication [112,113], and the acetylation of p53 is a critical mediator of antiviral response [244]. Interestingly, RSV treatment is known to activate p300 acetyltransferase to protect against rat spinal cord affected by sciatic nerve injury [245] and is also known to activate AMPK independent of SIRT1 in neurons [246] through yet unknown mechanisms. However, RSV activates AMPK in a poly-ADP-ribose polymerase 1 (PARP1)-dependent manner [71], which is also a potent inhibitor of SIRT1 [247].…”
Section: Rsv Is Also An Indirect Inhibitor Of Sirt1mentioning
confidence: 99%
“…Although SIRT1 is essential for coronavirus replication and survival [113], RSV instead inhibits coronavirus replication [112,113], and the acetylation of p53 is a critical mediator of antiviral response [244]. Interestingly, RSV treatment is known to activate p300 acetyltransferase to protect against rat spinal cord affected by sciatic nerve injury [245] and is also known to activate AMPK independent of SIRT1 in neurons [246] through yet unknown mechanisms. However, RSV activates AMPK in a poly-ADP-ribose polymerase 1 (PARP1)-dependent manner [71], which is also a potent inhibitor of SIRT1 [247].…”
Section: Rsv Is Also An Indirect Inhibitor Of Sirt1mentioning
confidence: 99%
“…In one of our previous publications, we observed that VEEV infection would lead to more necrosis than apoptosis in the same glioblastoma cell line, U87MG, indicating that the neural damage induced by VEEV can be robust and irreversible [ 48 ]. On the other hand, the mechanisms of neurological improvement facilitated by resveratrol have been recently depicted in numerous pieces of literature, including enhancement of autophagy, anti-oxidant effectiveness, and direct nerve regeneration [ 49 , 50 , 51 ]. As a result, the neuroprotectivity of resveratrol is worthy of further investigation as it relates to VEEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective action of resveratrol, an allosteric activator of SIRT1 [97], is well known [98] and, in several cases, it has been demonstrated that it acts through SIRT1 in this regard [99,100]. Two recent reports have also indicated that resveratrol treatment promoted axon regeneration in different models [101,102]. Resveratrol has, however, a myriad of known cellular targets [103,104], and in the above cases, its role in axon regeneration was attributed to other molecules rather than SIRT1 activation.…”
Section: Perspectivesmentioning
confidence: 99%